Challenges of Applying the SHEA/HICPAC Metrics for Multidrug-Resistant Organisms to a Real-World Setting - Furuya, E. Yoko (2011)
OBJECTIVE: To test in a real-world setting the recommendations for measuring infection with multidrug-resistant organisms (MDRO) from the Society for Healthcare Epidemiology of America (SHEA) and the Centers for Disease Control and Prevention’s Healthcare Infection Control Practices Advisory Committee (HICPAC). METHODS: Using data from 3 hospital settings within a healthcare network, we applied the SHEA/HICPAC recommendations to measure methicillin-resistant Staphylococcus aureus (MRSA) infection and colonization. Data were obtained from the hospitals’ electronic surveillance system and were supplemented by manual medical record review as necessary. Additionally, we tested (1) different definitions for nosocomial incidence, (2) the effect of excluding patients not at risk from the denominator for hospital-onset incidence, and (3) the appropriate time period to use when including or excluding patients with a prior history of MRSA infection or colonization from nosocomial rates. Negative binomial regression models were used to test for differences between rate definitions. A rating scale was created for each metric, assessing the extent to which manual or electronic data elements were required. RESULTS: There was no statistically significant difference between using 72 hours or 3 calendar days as the cutoff to define hospital-onset incidence. Excluding patients not at risk from the denominator when calculating hospital-onset incidence led to statistically significant increases in rates. When excluding patients with a prior history of MRSA infection or colonization from nosocomial incidence rates, rates were similar regardless of whether we looked at 1, 2, or 3 years’ worth of prior data. CONCLUSIONS: The SHEA/HICPAC MDRO metrics are useful but can be challenging to implement. We include in our description of the data sources and processes required to calculate these metrics information that may simplify the process for institutions.